ANALISIS PENGARUH PENGELUARAN PEMERINTAH DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA UTARA - Fatimah; Andiny, Puti; Rizal, Yani; Safuridar, Safuridar (Laboratorium Riset Ekonomi, 2024)
This study analyzes the impact of government spending and local revenue (PAD) on economic growth in North Sumatra for the period 2014-2023. The analytical method used is multiple linear regression, with t-tests and F-tests to determine the significance of the variables. The results indicate that government spending has a positive but insignificant effect on economic growth, with a coefficient of 2.83. In contrast, PAD shows a negative and significant effect on economic growth, with a coefficient of -2.08. Simultaneously, government spending and PAD have a significant influence on economic growth, with an R-squared value of 65.90%. These findings highlight the need for local governments to optimize spending and enhance the effectiveness of PAD in supporting sustainable economic development.